A comparative study of audio and visual reaction time in obese and non-obese subjects - Munawar, Ayesha; Aleem, Abdul (Asian Journal of Medical Sciences, 2021)
Background: Reaction time provides indirect index of processing capability of CNS and also a means of determining sensorimotor performance. The present study was undertaken to study and compare audio and visual reaction time in healthy obese subjects with non-obese subjects. Aims and Objectives: This prospective study was undertaken to find out whether obesity in otherwise healthy individuals is associated with any alteration in auditory and visual reaction time. Materials and Methods: The study involved 100 subjects 50 obese (cases) and 50 non-obese (control) of both sexes within age group 18-60 years. The Anthropometric parameters under study are height in meters, weight in kg to calculate BMI. Then we measured auditory reaction time (ART) and visual reaction time (VRT) and compared in 2 groups. This comparative study was carried out in Dr. S.C.G.M.C, Vishnupuri, Nanded. Results: We have found that auditory and visual reaction time was longer in obese subjects than non-obese control. There was a significant increase in (P<0.05) ART to sufficient sound and significant increase in VRT(P<0.001) to yellow color. Conclusion: We conclude that there is evidence of sensory motor slowing and delay in CNS processing in obesity as suggested by increased reaction time to audiovisual stimuli.